Automobile Road and Climatic Zoning of the Belarus Territory and Efficiency of Transport Service - D. D. Selioukov; I. I. Leonovich (Наука и техника)
In order to improve road safety on automobile roads it is necessary to take into account weather and climatic factors. These factors vary within significant limits in the Republic of Belarus. The paper justifies zoning of the Republic territory that is designed to control transport and operational state of the roads.